Evaluation of efficacy, biodistribution and safety of antibiotic-free plasmid encoding somatostatin genes delivered by attenuated Salmonella enterica serovar Choleraesuis - Liang, Aixin; Riaz, Hasan; Dong, Fangxiao; Luo, Xuan; Yu, Xue; Han, Yanguo; Chong, Zhenlu; Han, Li; Guo, Aizhen; Yang, Liguo (Vaccine, 2014)
•Asd-based balanced-lethal system for DNA vaccine was evaluated in this paper.•The C501(pVGS/2SS-asd) vaccine could induce systemic and mucosal immune responses.•The C501 (pVGS/2SS-asd) vaccine is safe and stable for clinical use in large animals.•The risk of gene integration into the host cellular genome was negligible. We describe here a balanced-lethal system using an Asd+ expression plasmid pVGS/2SS-asd encoding two copies of somatostatin (SS) genes carried by Δasd/Δcrp double mutant Salmonella enterica serovar Choleraesuis (named C501). The advantage of this novel system is the use of asd (aspartate-semialdehyde dehydrogenase) gene as selection marker to replace the antibiotic resistance markers, thus eliminating the industrial cultivation and environmental problems. We then evaluated the efficacy, biodistribution and safety of antibiotic-free plasmid delivered by strains C501. Mice orally immunized with C501 (pVGS/2SS-asd) had significantly higher levels of anti-SS total IgG and IgA antibodies than control mice and demonstrated a bias toward Th2-associated responses (IgG1/IgG2a ratio>1). Safety evaluation indicated that vaccinated mice displayed no abnormal clinical signs and histological changes. Biodistribution result revealed that the GS/2SS message was detected in several examined tissues with the exception of ovary and brain, but was rapidly cleared from the body (approximately 10 days). Furthermore, the risk of integration of plasmid pVGS/2SS-asd into the host cellular genome was considered to be negligible. These results may have important implications for the use of vaccine strain C501 (pVGS/2SS-asd) in domestic animals and prompt new perspectives on the safety of DNA vaccines delivered by attenuated bacteria.